1981
DOI: 10.1111/j.1365-2494.1981.tb01545.x
|View full text |Cite
|
Sign up to set email alerts
|

The development and use of equipment for the automatic recording of ingestive behaviour in sheep and cattle

Abstract: A description is given of equipment designed to be fitted to either sheep or cattle, and to record automatically information on the jaw movements associated with both grazing and ruminating, movements ofthe head in plucking mouthfuls of herbage, and the time spent in grazing. The equipment has been successfully tested against alternative visual and mechanical methtxls of measuring grazing behaviour.The use of modified equipment in detailed studies has shown (a) that the maximum acceleration of the head in a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…If tiller length is viewed as a moment arm, the distance and angle perpendicular to the tiller, from the tiller's rooted position to that at severance will increase with sward height and/or tensile strength, implying that displacement and acceleration are important components of biting effort. In support, Chambers et al [16] found that the rate of head acceleration of sheep decreased with increasing sward height. However, these authors did not observe a similar pattern for cattle.…”
Section: Effort Vs Forcementioning
confidence: 84%
See 2 more Smart Citations
“…If tiller length is viewed as a moment arm, the distance and angle perpendicular to the tiller, from the tiller's rooted position to that at severance will increase with sward height and/or tensile strength, implying that displacement and acceleration are important components of biting effort. In support, Chambers et al [16] found that the rate of head acceleration of sheep decreased with increasing sward height. However, these authors did not observe a similar pattern for cattle.…”
Section: Effort Vs Forcementioning
confidence: 84%
“…Chambers et al [16] reported the rate of head acceleration as some 65% greater for sheep than for cattle grazing the same sward. There is little quantification of the effort and associated costs incurred in upholding the tension in the muscles of the neck to maintain the head momentum, although Illius et al [42] comment that it must be considerable.…”
Section: Effort Vs Forcementioning
confidence: 98%
See 1 more Smart Citation
“…One way which this technological advancement can help advance an understanding of pastoral livestock-environment interactions is to couple GPS data with 'vibracorders' and digital pedometers in order to infer grazing behaviors of cattle (Castle et al, 1975;Chambers et al, 1981;Ungar et al, 2005). This would reduce the amount of labor required to document behaviors and would increase the accuracy and independence of the data.…”
Section: Efficacy Of the Gps Tracking Methods And Technological Improvmentioning
confidence: 98%
“…Under conditions where animals are able to browse or are grazing on slopes, the use of head position (Stobbs and Cowper, 1972;Chambers <? ( a/., 1981) could lead to errors in estimating grazing and ruminating time and total jaw movements associated with these activities.…”
Section: Discussionmentioning
confidence: 99%